MENINGKATKAN SIKAP BERPIKIR KRITIS SISWA SMP MELALUI LKS BERBASIS INKUIRI - Laila Khusnah (JURNAL BIOSHELL, 2016)
Improving thestudents’ critical thingking attitude by using an inquiry-based students’ worksheet becomes the research objective by using 4D model development research design from Thiagarajan. The worksheet is validated by the expert andthe science teacher, and then it’s practically tested to thejunior high school students of class VIII. The validation resultsshow that the worksheet is categorized sufficiently valid. So even also with the results ofpractical test indicating that the worksheet is effectively used on learning process because of improving the students’ critical thingking attitude.Keywords: critical thinking attitude, inquiry-based worksheet, inquiry method.